Analysis of echocardiographic criteria for pulmonary embolism - A. G. Pronin; N. Y. Sivokhina; M. A. Goncharov (Вестник медицинского института «Реавиз»: Реабилитация, врач и здоровье)
To date, the search for the most informative diagnostic and prognostic echocardiographic criteria for pulmonary embolism is relevant. Aims. To conduct a critical analysis of the generally accepted echocardiographic criteria for pulmonary embolism in order to establish the most significant of them in determining the severity and outcomes of the disease. Materials and methods. The study included 42 patients with fatal pulmonary embolism, 51 patients with hemodynamically unstable and 193 with hemodynamically stable course of the disease. The prevalence of generally accepted echocardiographic criteria for overload of the right heart was assessed, followed by their significance for determining the severity of the disease and predicting its outcomes. Results. It was found that among the generally recognized echocardiographic criteria, the most significant for determining the severity of pulmonary embolism and its outcomes are: an increase in the ratio of basal sizes of the right and left ventricles more than 1.1, an increase in systolic pressure in the pulmonary artery more than 55 mm Hg, dyskinesia of the free wall of the right ventricle, flattening of the interventricular septum, a decrease in systolic excursion the plane of the tricuspid valve is less than 1.6 cm. However, all of them, except the last one, do not have high sensitivity and specificity. The significance of the currently underestimated cardiac stroke volume as a prognostic indicator of echocardiography has been established. It was determined that its decrease of less than 45 ml correlated with hemodynamic instability of the course of the disease, and less than 35 ml was associated with a fatal outcome. This indicator had high diagnostic characteristics. Conclusion. A decrease in the systolic excursion of the tricuspid valve plane of less than 1.6 cm and a decrease in the stroke volume of the heart of less than 45 ml are the most significant indicators of echocardiography in assessing the severity and prognosis of pulmonary embolism.